BIMBINGAN TEKNIS SISTEM IRIGASI TETES WILAYAH POKJA KARANGLO INDAH, KECAMATAN BLIMBING, KOTA MALANG - Sunik; Rahmanti Ignatia, Sari Perwita; Harsa Dhani; Sendy Fransiscus Tantono (LPPM Unika Widya Karya Malang, 2024)
Vegetable crops need sufficient water to support growth. Lack or excess of water will cause stunted growth and even death of plants due to dryness or root rot. Appropriate irrigation technique is the key success in cultivating vegetable crops. Kelompok Kerja (Pokja) RT 01 RW 04, Karanglo Indah has a work program, namely women empowerment in supporting family food availability, by cultivating vegetables in the house yard. The problem is in watering. Technical guidance is provided through presentation, discussion and demonstration activities. Presentation and discussion aim to increase knowledge and comprehension of irrigation systems, equipment procurement, installation procedures, operating and maintenance procedures for drip irrigation. The demonstration aims to improve skills in carrying out procedures that have been presented in the presentation and discussion. The results obtained are increased knowledge, comprehension and skills for implementing drip irrigation so that better quality vegetables are produced.